Acute Oxygen-Sensing via Mitochondria-Generated Temperature Transients in Rat Carotid Body Type I Cells - Rakoczy, Ryan J.; Schiebrel, Clay M.; Wyatt, Christopher N. (Frontiers in Physiology, 2022)
The Carotid Bodies (CB) are peripheral chemoreceptors that detect changes in arterial oxygenation and, via afferent inputs to the brainstem, correct the pattern of breathing to restore blood gas homeostasis. Herein, preliminary evidence is presented supporting a novel oxygen-sensing hypothesis which suggests CB Type I cell “hypoxic signaling” may in part be mediated by mitochondria-generated thermal transients in TASK-channel-containing microdomains. Distances were measured between antibody-labeled mitochondria and TASK-potassium channels in primary rat CB Type I cells. Sub-micron distance measurements (TASK-1: 0.33 ± 0.04µm, n=47 vs. TASK-3: 0.32 ± 0.03µm, n=54) provided evidence for CB Type I cell oxygen-sensing microdomains. A temperature-sensitive dye (ERthermAC) indicated that inhibition of mitochondrial activity in isolated cells caused a rapid and reversible inhibition of mitochondrial thermogenesis and thus temperature in these microdomains. Whole-cell perforated-patch current-clamp electrophysiological recordings demonstrated sensitivity of resting membrane potential (Vm) to temperature: lowering bath temperature from 37°C to 24°C induced consistent and reversible depolarizations (Vm at 37°C: -48.4 ± 4.11mV vs. 24°C: -31.0 ± 5.69mV; n=5; p<0.01). These data suggest that hypoxic inhibition of mitochondrial thermogenesis may play an important role in oxygen chemotransduction in the CB. A reduction in temperature within cellular microdomains will inhibit plasma membrane ion channels, influence the balance of cellular phosphorylation–dephosphorylation, and may extend the half-life of reactive oxygen species. The characterization of a thermosensory chemotransduction mechanism, that may also be used by other oxygen-sensitive cell types and may impact multiple other chemotransduction mechanisms is critical if we are to fully understand how the CBs, and potentially other oxygen-sensitive cells, respond to hypoxia.